Wisdom behind the popularity of Recep Tayyip Erdogan’s leadership in the Muslim World - Kayadibi, Saim; Kayadibi, Yasemin (2012)
Muslim world, particularly the Middle East face crisis of leadership for the last century, has been struggling with leaders who are not in concern of their own peoples’ problems, not protecting and looking for the interests of their country and the Ummah in general. Therefore, Muslim societies still remain as colony of the Westerners in terms of cultural and political, despite of physically being freed as colonized countries; they are suffocated from the rulers’ repression, persecution and dictatorship, which brought the peoples to the verge of serious social explosions. With Recep Tayyip Erdoğan’s sitting on the Prime Ministry seat by the 2002 general elections, in which democratization process has been almost completed in Turkey, became a starting point for serious changes not only in the Muslim world but also in the whole world. The new Prime Minister, who have completed his self-confidence, besides Turkey’s domestic affairs, he took the Muslim world’s common problems as priorities in his agenda. A major recent survey of public opinion in Arab countries show that Turkey is viewed as having played the “most constructive” role in the past year’s events and the prime minister of it, Recep Tayyip Erdoğan (RTE), emerged as “the most admired world leader”, “the most welcomed world leader”, “the most constructive leader” in the region. Accordingly, these made Arab world to consider Turkey as really the model country for them in terms of its system of internalizing the concept of democracy and free elections. Hence, Turkey became a unique country in terms of providing peaceful environment for both secularism and Islam that represents 99 % of the population. Despite of the fact that, there must be cultural, social and historical reasons behind this reality, however, Arab world consider Turkey as the model country and its leader is the model leader for the Muslim world. In this research, the reasons behind the success of RTE and the popularity of Turkey, as a model country for Muslim world, will be investigated. Thus, it’s hoped that this research would provide substantial contributions to the Muslim societies who are struggling to revitalize their dynamics in order to choose their own leaders among them and create their own civilizational parameters and values. Keywords: Leadership; Recep Tayyip Erdoğan; Social Change; Muslim World.